2019
DOI: 10.1016/j.jhep.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Different techniques for ultrasound liver elastography

Abstract: Shear wave Single acoustic ultrasound push pulse *ROI Ultrasound wave Pulse wave *ROI *Selected small (10x5 mm) region of interest (ROI). ROI can be freely moved anywhere in the scanning plane up to 8 cm in depth to capture shear wave speed. 0-5 kPa no significant fibrosis (regardless of the machine). Range from 5-6 to 13-17 kPa includes thresholds to distinguish different fibrosis stages (F2-F3-F4). Precise threshold depends on specific technologies/manufacturers and liver disease etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Liver ultrasound elastography is suitable as non-invasive assessment tool. There are different techniques available within liver ultrasonography, such as vibration-controlled transient elastography (TE), two-dimensional shear-wave elastography (2D-SWE) and point shear-wave elastography (pSWE) (69). These methods are broadly similar, but differ in terms of technical principles and sampling rate (70).…”
Section: Discussionmentioning
confidence: 99%
“…Liver ultrasound elastography is suitable as non-invasive assessment tool. There are different techniques available within liver ultrasonography, such as vibration-controlled transient elastography (TE), two-dimensional shear-wave elastography (2D-SWE) and point shear-wave elastography (pSWE) (69). These methods are broadly similar, but differ in terms of technical principles and sampling rate (70).…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study showed only moderate concordance of different SWE techniques with TE results for the staging of significant fibrosis, suggesting that TE thresholds cannot be directly transferred to other elastography machines [41]. Consequently, specific thresholds for fibrosis staging, ≥F2 in particular, would be required for each specific piece of equipment grounded on scientific research [40]. Nonetheless, the optimal cutoff values proposed for 2D SWE varied across the published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, TE is considered as an alternative to biopsy and a reference technique for defining fibrosis staging for other novel SWE technologies, including 2D SWE [40]. However, a previous study showed only moderate concordance of different SWE techniques with TE results for the staging of significant fibrosis, suggesting that TE thresholds cannot be directly transferred to other elastography machines [41].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative imaging is performed using mechanical forces or intrinsic internal forces, whereas quantitative imaging is generally performed through the application of force produced by an ultrasound probe [26]. The 3 ultrasound elastography methods in use today are TE; point shear wave elastography (pSWE), also known as acoustic radiation force impulse quantification; and 2-dimensional shear wave elastography (SWE) (Figure 3) [27,28]. SWE uses qualitative and quantitative techniques (Figure 4) [26].…”
Section: Ultrasound Elastographymentioning
confidence: 99%
“…TE, transient elastography; SWE, shear wave elastography; pSWE, point shear wave elastography; ROI, region of interest; ULN, upper limit of normal; HBV/HCV, hepatitis B virus/hepatitis C virus. (Image reproduced from Mulazzani et al[28] with permission from Elsevier. )…”
mentioning
confidence: 99%